Contribuição à oncologia comparada em Minas Gerais - Rangel, N M; Machado, A V (Revista Ceres, 1942)
The Aa. make the first report about the incidence of spontaneous tumors of domesticated in the State of Minas Gerais, Brazil, collected at the Department of Histology and Pathology of the Minas Gerais State Veterinary School. Among 882 pathological specimens there were 146 tumors. Most of the specimes came from bovines, swine and fowls. The incidence of tumors in swine was very low. Most of the tumors were from bovine and fowls, and, secondarily, from horses, dogs and others. The Aa. summarise the incidence, into 16 tables, by species, by variety of tumor and by organs.